Beyond the Dusty Fog: Local Eye Drop Therapy and Potentially New Treatment Alternatives in Pseudoexfoliative Glaucoma - Zeppieri, Marco; Musa, Mutali (Current Medicinal Chemistry, 2024)
Pseudoexfoliative glaucoma (PEG) is a type of secondary open-angle glaucoma characterized by the accumulation of whitish-gray material on the trabecular meshwork and lens, leading to an increase in intraocular pressure (IOP) and optic nerve damage. Local eye drop therapy is one of the first-line treatments for PEG, which include prostaglandin analogues, beta-blockers, and alpha-adrenergic agonists to lower IOP. New treatments beyond conventional techniques, however, are constantly being developed. One potential treatment proposed for PEG is based on magnetic phage display, which involves using magnetic nanoparticles conjugated to specific peptides or proteins selected using phage display techniques to remove aggregates in the anterior chamber of the eye or inflammatory cells and cytokines that contribute to PEG pathogenesis. Other potential treatments include microRNAs (miRNAs) that are involved in the regulation of gene expression at the post-transcription stages. Gene therapies, nanotechnology, immunotherapy and methods based on stem cells can also be potentially used to target and treat specific tissues and cells responsible for regulating IOP. In addition, photobiomodulation therapy (PBMT), a non-invasive procedure that utilizes low-level laser therapy to improve cellular function and promote tissue repair, can prove an interesting alternative in treating PEG. The aim of our mini-review is to provide a brief overview of these innovative methods that appear to offer potentially promising treatment options for PEG.
Keywords: Pseudoexfoliative glaucoma (PEG)